New agricultural trends in the use of blueberries for a new lifestyle (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
"New agricultural trends in the use of blueberries for a new lifestyle."The purpose of the research is to develop a comparative socioeconomic study of blueberry cultivation in the municipality of Tenjo Cundinamarca, through a productive model according to the determinants focused for the development of blueberry cultivation in the municipality of Tenjo where it is intended to create new processes manual in each of the areas required by the project, such as in the planting area, the cultivation area, the area of (MIPE) integrated management of pests and diseases, in the area of (MIRFE) integrated management of irrigation and fertilizer, In the area of production and in everything involved in the process of marketing the final product and thus reach the community of the village of Carrasquilla and generate a better economic development for more than thirty families, since generating a viable and sustainable blueberry project will improve the economic development of the farmers in the region, with this project is intended to make known to all people the benefits of a viable and sustainable business, well structured and which is intended to make the best profit starting in the municipality of Tenjo Cundinamarca in the village of carrasquilla but with a purpose to take it to a growth where it can be generated in many of the regions of Colombia, and thus to contribute to a better lifestyle for all those people who make part of the project.